Factors influencing vaccination of dogs against rabies in South Mugirango Sub-County-Kisii County; Kenya. - Fanice Kerubo Obara; Eric Omori Omwenga; Japheth Mativo Nzioki; Lameck Ondieki Agasa (PLOS Global Public Health)
Rabies is a fatal zoonotic viral disease affecting all warm-blooded mammals, with approximately 99% of human cases resulting from bites by infected dogs. This study assessed the factors influencing dog vaccination against rabies in South Mugirango, Kisii County, Kenya, where the disease remains endemic and a major public health concern. A quantitative descriptive cross-sectional survey was conducted, utilizing structured questionnaires administered to 422 household heads. Additionally, 22 key informant interviews were carried out with officials from relevant government departments to gain deeper insights. This was a mixed method study involving both a cross sectional survey and qualitative data collection. Data were analyzed using appropriate statistical techniques to identify patterns and determine associations between socio-demographic factors and vaccination practices. Socio-demographic factors significantly associated with rabies awareness included marital status (p = 0.049), occupation (p = 0.029 for housewives), and the gender of the household breadwinner (p = 0.017 for males). Despite high awareness levels, 4.1% (17/422) of respondents had not vaccinated their dogs in the past year, and only 15.9% (67/422) reported recent vaccinations. Older individuals were 12% more likely to vaccinate their dogs per year of age (OR = 1.12, p = 0.002). Higher education (OR = 1.45, p = 0.010), income (OR = 1.20, p = 0.008), rabies awareness (OR = 2.30, p < 0.001), and access to veterinary services (OR = 1.75, p < 0.001) significantly improved adherence. Despite high awareness, dog vaccination rates in South Mugirango remain low, highlighting the need for targeted interventions. Expanding access to veterinary services, subsidizing vaccines, and prioritizing outreach to younger individuals, less-educated and female-headed households can improve vaccination adherence and reduce rabies transmission.